Anti Skolem Mean Labeling of Alternate Triangular Snake Graphs (International Journal of Food and Nutritional Sciences, 2022)
A graph G = (V, E) with p vertices and q edges where p < q + 1 is said to be an Anti Skolem Mean graph if it is possible to label the vertices x  V with distinct labels f(x) from {1, 2, …, q + 1} in such a way that when each edge e = uv is labeled with f(e= uv)= (f(u)+ f(v))/2 if f(u) + f(v) is even and (f(u)+f(v)+1)/2 if f(u) + f(v) is odd then the resulting edges are distinct labels from the set {2, 3, . . . , p}. In this case f is called an Anti Skolem Mean labeling of G. In this paper, we prove that Alternate Triangular Snake Graphs are Anti Skolem Mean graphs.